Sexual violence victim-witnesses at the Special Court for Sierra Leone: Have lessons from ICTR been learnt? - Kweka, Gift Joseph (Department of Public Law, 2014)
Rape and other forms of sexual violence are increasingly becoming the order of the current armed conflicts of both internal and international characters no matter what the reasons behind the conflicts are. These inhuman acts are mostly committed against female civilian population by male soldiers from the government armed forces, rebel groups, paramilitary groups and even peace keeping forces. The countries whose armed conflicts were characterised by acts of rape and sexual violence include; Rwanda, Democratic Republic of Congo, Somalia, Uganda, Sudan, Yugoslavia (Bosnia and Herzegovina), East Timor, to mention just a few.